Fusion of an intact secretory protein permits a misfolded protein to exit from the endoplasmic reticulum in yeast. Issue 1 (2nd January 2014) - Suyama, Kengo; Hori, Mizue; Gomi, Katsuya; Shintani, Takahiro
Abstract: Upon exit from the endoplasmic reticulum (ER), the nascent polypeptides of secretory proteins undergo sorting events. If properly folded, they are directly or indirectly recognized by the coat proteins of budding vesicles for forward transport, while unfolded or misfolded proteins are retained in the ER by a quality control mechanism. To gain insight into the interplay between ER export and ER quality control, we fused a secretory protein invertase to the C-terminus of mutated carboxypeptidase Y (CPY*), a model ER-associated degradation (ERAD) substrate in Saccharomyces cerevisiae . This substrate, designated CPY*-Inv, was largely exported from the ER, although it was fully recognized by the ERAD-related lectin, Yos9, and hence degraded by the ERAD when it remained in the ER. CPY*-Inv relied primarily on the p24 complex, a putative ER export receptor for invertase, for escape from ERAD, suggesting that the ERAD and the ER export of soluble secretory proteins are competitive. Graphical abstract: : In the endoplasmic reticulum (ER), ERAD machineries and export receptors compete secretory proteins to determine whether they are degraded or exported from the ER.